Monoclonal antibodies against the haemagglutinin-neuraminidase glycoprotein of Newcastle disease virus strain AF2240 - Lee, L. K.; Eshaghi, Majid; Ali, Abdul Manaf; Mohd Yusoff, Khatijah (Veterinary Association Malaysia, 2007)
The Malaysian velogenic-viscerotropic Newcastle disease virus (NDV) strain AF2240 is the reference strain that has often been used for vaccine development. Eight hybridoma clones producing monoclonal antibodies (mAbs) against NDV strain AF2240 were established as a result of fusion between myeloma Sp2/0-Ag14 and Balb/c B-lymphocytes. Isotyping of mAbs showed that clones 1B9, 2D6 and 9D7 produced IgG1, clones ID5, 5A10 and 5F10 produced IgG2a and clones 2G3 and 5E10 produced IgG3. All the mAbs possessed kappa (K) light chain. The mAbs were reacted towards the haemagglutinin-neuraminidase (HN) glycoprotein of the virus and able to inhibit in the haemagglutination with chicken red blood cells but not the haemolysis-inhibition test which confirmed that they were specific to the HN glycoprotein and not to fusion protein.